Selective and sensitive sensing of free bilirubin in human serum using water-soluble polyfluorene as fluorescent probe - Senthilkumar, T.; Asha, S. K. (Macromolecules, 2015)
The adherence of serum protein on conjugated polymer is a major bottleneck in the application of the latter for selective sensing of small biomolecules in blood serum. In this report, we present new polyfluorenes with d-glucuronic acid appendage that is a nonreceptor for any serum protein, thereby providing a platform for selective sensing of free bilirubin in the clinically relevant range of <25 to >50 mu mol/L in human blood serum. The appended d-glucuronic acid formed noncovalent interactions with bilirubin, which in conjunction with favorable spectral overlap between the polymers and bilirubin facilitated efficient FRET process in aqueous solutions. Addition of bilirubin resulted in the quenching of the polyfluorene emission with simultaneous appearance of bilirubin emission exhibiting visual emission color change from blue to light green. The polymer remained stable in serum even under severe basic conditions and exhibited high selectivity with visual sensitivity only toward free bilirubin in human serum in the presence of crucial interferences such as hemoglobin, proteins, biliverdin, glucose, cholesterol, and metal ions. Nanomolar sensing of bilirubin could also be demonstrated successfully using one of the d-glucuronic acid appended polymer (PF-Ph-GlcA), which could sense similar to 150 nm of bilirubin in human serum. The combined role of energy transfer and noncovalent interaction highlights the potential of the new polymer design for highly selective sensing activity in complex biofluids.